Direct Ink Writing of Moldable Electrochemical Energy Storage Devices: Ongoing Progress, Challenges, and Prospects. Issue 7 (19th March 2021) - Zhang, Quanhai; Zhou, Jiangqi; Chen, Zhihong; Xu, Chao; Tang, Wei; Yang, Guangzhi; Lai, Chunyan; Xu, Qunjie; Yang, Junhe; Peng, Chengxin
Abstract : Among the advanced additive manufacturing technologies, direct ink writing (DIW) technology is extensively utilized to fabricate various energy storage devices (i.e., batteries, supercapacitors [SCs], and solar cells) due to its excellent process flexibility, excellent geometric controllability, as well as relative low‐cost and efficient processes. DIW offers a convenient way to build 3D structures for energy storage devices and provide higher power density and energy density in comparison with traditional casting techniques. Herein, the recent advances in DIW for emerging energy storage devices, including SCs, lithium‐ion batteries, lithium–sulfur batteries, rechargeable lithium metal batteries, and solid‐state batteries, are emphasized and discussed. The significant achievements made developing printed energy storage devices, such as printing ink materials, designing the printing process, and the great progress in terms of the corresponding electrochemical performances, are also highlighted. Finally, the major challenges and potential research possibilities in 3D printing energy storage device are proposed. It can be expected that, as 3D printing technology develops, batteries and SCs with durable lifespans, favorable safety, as well as high energy density and power density will eventually be utilized in many fields. Abstract : The review summarizes the direct ink writing (DIW) of moldable electrochemical energy storage devices, including printed electrode materials, electrolyte materials, the structural designs and applications of printed supercapacitor and batteries, and guidelines on how to practically design materials and structures via the DIW technique for future energy storage devices.